2017
DOI: 10.1016/j.cotox.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity as opportunity: Insights from 600 million years of AHR evolution

Abstract: The aryl hydrocarbon receptor (AHR) was for many years of interest only to pharmacologists and toxicologists. However, this protein has fundamental roles in biology that are being revealed through studies in diverse animal species. The AHR is an ancient protein. AHR homologs exist in most major groups of modern bilaterian animals, including deuterostomes (chordates, hemichordates, echinoderms) and the two major clades of protostome invertebrates [ecdysozoans (e.g. arthropods and nematodes) and lophotrochozoans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 147 publications
7
114
0
3
Order By: Relevance
“…There is a general consensus that the AhR of modern humans is implicated in DNA repair (Dittmann et al, ; Schreck et al, ), tumor suppression (Fan et al, ; Yu et al, ), epidermal barrier function (Noakes, ), skin tanning response, and melanocyte homeostasis (Jux et al, ; Luecke et al, ). Phylogenetic analysis suggested that the ability of vertebrate AhR to sense xenobiotics was acquired at a late stage of evolution, implying that the driving force for evolutionary conservation of AhR lies not only in its role in xenobiotic metabolism but also in normal cell development (Hahn et al, ; Hao & Whitelaw, ).…”
Section: The Role Of the Ahrmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a general consensus that the AhR of modern humans is implicated in DNA repair (Dittmann et al, ; Schreck et al, ), tumor suppression (Fan et al, ; Yu et al, ), epidermal barrier function (Noakes, ), skin tanning response, and melanocyte homeostasis (Jux et al, ; Luecke et al, ). Phylogenetic analysis suggested that the ability of vertebrate AhR to sense xenobiotics was acquired at a late stage of evolution, implying that the driving force for evolutionary conservation of AhR lies not only in its role in xenobiotic metabolism but also in normal cell development (Hahn et al, ; Hao & Whitelaw, ).…”
Section: The Role Of the Ahrmentioning
confidence: 99%
“…There is a general consensus that the AhR of modern humans is implicated in DNA repair (Dittmann et al, 2016;Schreck et al, 2009), tumor suppression (Fan et al, 2010;Yu et al, 2017), epidermal barrier function (Noakes, 2015), skin tanning response, and melanocyte homeostasis (Jux et al, 2011;Luecke et al, 2010). Phylogenetic analysis suggested that the ability of vertebrate AhR to sense xenobiotics was acquired at a late stage of evolution, implying that the driving force for evolutionary conservation of AhR lies not only in its role in xenobiotic metabolism but also in normal cell development (Hahn et al, 2017;Hao & Whitelaw, 2013). Hubbard et al (2016) showed that the AhR variant in modern humans contains Val381 residue in the ligandbinding domain, while the AhR of Neanderthals, and a Denisovan individual, as well as nonhuman primates and other vertebrates (rodents) encode the ancestral Ala381 variant.…”
Section: The Role Of the Ahrmentioning
confidence: 99%
“…A major difference is in the number of AHR genes. In contrast to the single AHR gene present in most mammals, fish (and most other vertebrates) have multiple AHR genes (Hahn, Karchner, & Merson, 2017;Hahn et al, 2006). Fish typically have four AHR genes, products of a tandem gene duplication (AHR1 and AHR2) and paralogs of each of these (designated "a" and "b"), the result of a whole-genome duplication at the base of the teleost lineage, after its divergence from the lineage leading to tetrapods (Goodale et al, 2012;Incardona et al, 2006).…”
Section: Ahr Variation Among Vertebrates and Role In Differential Smentioning
confidence: 99%
“…Although AhR proteins have been identified in numerous organisms within the kingdom Animalia (but not outside it), the ability to bind planar aromatic hydrocarbons with high affinity appears to be unique to vertebrates [15]. Leishmania organisms are eukaryotes, but as trypanosomes they are classified outside the kingdom Animalia, and an AhR has not been reported to exist within them.…”
Section: Discussionmentioning
confidence: 99%